The production of subjectivity : Marx and philosophy - Read, Jason (Leiden ; Boston : Brill, 2022)
"Louis Althusser argued that Marx initiated a transformation of philosophy, a new way of doing philosophy. This book follows that provocation to examine the way in which central Marxist concepts and problems from primitive accumulation to real abstraction animate and inform philosophers from Theodor Adorno to Paolo Virno. While also examining the way in which reading Marx casts new light on such philosophers as Spinoza. At the centre of this transformation is the production of subjectivity, the manner in which relations of production produces ways of thinking and living"--
Primitive accumulation : the aleatory foundation of capitalism -- The present as pre-history : Adorno and Balibar on the transformation of labor -- The Althusser effect : philosophy, history, and temporality -- To think the new in the absence of its conditions : Althusser and Negri on the philosophy of primitive accumulation -- A universal history of contingency : Deleuze and Guattari on the history of capitalism -- The age of cynicism : Deleuze and Guattari on the political logic of contemporary capitalism -- The fetish is always actual, revolution is always virtual : Marx and Deleuze -- The affective economy : producing and consuming affects in Deleuze and Guattari -- Beyond enslavement and subjection : deviations from Deleuze and Guattari -- The potentia of living labour : Negri's practice of philosophy -- The order and connection of ideas : theoretical practice in Macherey's turn to Spinoza -- Desire is man's very essence : Spinoza and Hegel as philosophers of transindividuality -- The order and connection of ideology is the same as the order and connection of exploitation : or, towards a bestiary of the capitalist imagination -- Conscienta sive ideologica : on the spontaneity of ideology -- A genealogy of homo-economicus : Foucault, neoliberalism, and the production of subjectivity -- Abstract materialism : Alfred Sohn-Rethel and the task of materialist philosophy -- The production of subjectivity : from transindividuality to the commons -- Man is a werewolf to man : capital and the limits of political anthropology -- The 'other scene' of political anthropology : between transindividuality and equaliberty -- Anthropocene and anthropogenesis : philosophical anthropology and the ends of man.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 19, 2022).
eBooks on EBSCOhost
Keywords: Marx, Karl, -- 1818-1883.; Marx, Karl, -- 1818-1883; Philosophy, Marxist; Philosophy, Modern; Subjectivity; Philosophy, European; Philosophie européenne.; Philosophie marxiste; Philosophy, European; Subjectivity; Criticism, interpretation, etc